Does the serum vitamin D status and its possible effect on serum anti-müllerian hormone levels predict fertility in premenopausal women? - Oyinkansola Islamiyat Lawal (Wolters Kluwer Medknow Publications, 2021)
Context: Evidence suggests that serum Vitamin D level influences female reproduction. However, clinical studies have reported conflicting evidence on the effect of serum Vitamin D levels on serum Anti-Müllerian hormone (AMH), with little evidence in African women. Aim: The study aimed to compare the relationship between serum Vitamin D and serum AMH among infertile and fertile women. Settings and Design: This comparative cross-sectional study analyzed data from 170 premenopausal women; 81 infertile, and 89 fertile women attending a Nigerian tertiary hospital between March and June 2019. Materials and Methods: Serum AMH and 25-hydroxyvitamin D (25(OH) Vitamin D) concentrations were analysed using enzyme-linked immunosorbent assay. Statistical Analysis: Statistical analysis was done using SPSS version 25 for windows. Categorical variables were summarized in frequencies and proportions while continuous variables were summarized in means ± standard deviation and median (interquartile range). The association was explored using linear regression. The level of significance was set at 0.05. Results: The prevalence of Vitamin D deficiency (<20 ng/ml) in infertile women and fertile women was 16% and 18%, respectively. There was no difference in serum Vitamin D levels between infertile and fertile women in this study after controlling for age and body mass index (BMI) (P = 0.186). There was no association between serum 25(OH) Vitamin D and serum AMH in infertile (B = 0.002; P = 0.474) and fertile women (B = ‒0.002; P = 0.522) after adjusting for age and BMI. Conclusion: Infertile and fertile women had similar serum Vitamin D levels and there was no relationship between serum Vitamin D and serum AMH in both infertile and fertile women.